Implications of critical success factors for digital transformation in Vietnam using a hybrid neutrosophic analytic hierarchy process - Hoai Bac Dang; Trong Phong Vu; Thi Thai Quynh Pham; Phuoc Van Nguyen (International Journal of Sustainable Engineering, 2024)
The digital transformation of Vietnam is a crucial strategic priority for the country’s rapid and sustainable development. This article presents a new method that combines the neutrosophic analytical hierarchy process (NAHP) with the technique for order of preference by similarity to ideal solution (TOPSIS) to analyse the impact of critical success factors (CSFs) on digital transformation. The NAHP was employed to ascertain the weights of the criteria, which serve as the most important indications of success in digital transformation. After obtaining the criteria weights, the alternatives were ranked based on their performance relative to the criteria provided by the TOPSIS technique. With the success of digital transformation activities, firms have substantial acceptance of the reliability of technological, organisational, and environmental (TOE) factors. The study investigated several factors, including leadership, organisational culture, technology infrastructure, and customer-centricity. The proposed methodology required evaluation by implementing a practical case study involving TOE critical factors in the Vietnamese digital transformation sector. Several methodologies and multi-criteria approaches have been developed to assess the key factors that contribute to the successful digital transformation of enterprises. The findings highlighted the validity of the hybrid NAHP-TOPSIS methodology in determining CSFs necessary for achieving objectives relevant to digital transformation.